(untitled) - Pyne, Stephen J. (Washington, 2004)
Tending Fire provides a remarkably broad, sometimes startling context for understanding fire. Pyne traces the "ancient alliance" between fire and humanity, delves into the role of European expansion and the creation of fire-prone public lands, and then explores the effects wrought by changing policies of "letting burn" and suppression. How, the author asks, can we better protect ourselves against the fires we don't want, and better promote those we do?
Keywords: Fire management,Quản lý hỏa hoạn; History,Lịch sử; United States,Hoa Kỳ